The human papillomavirus Test of Cure: A lesson on compliance with the NHMRC guidelines on screening to prevent cervical cancer - Munro, A.; Spilsbury, Katrina; Leung, Y.; O'Leary, Peter; Williams, Vincent; Codde, J.; Steel, N.; Cohen, P.; Semmens, James (Wiley-Blackwell Publishing Asia, 2015)
Background - In Australia, high-risk human papillomavirus (HR HPV) testing is recommended for follow-up of women treated for a high-grade squamous intra-epithelial lesion (HSIL). The sensitivity of HR HPV testing is critical to identify women at risk of further high-grade cervical disease. In Australia, this management protocol is known as the ‘Test of Cure’ (ToC). Aim - To conduct a population-based study investigating practitioners' compliance with ToC. Materials and Methods - Women treated for an HSIL between the five-year period 01 Jan 2006 to 31 Dec 2010 were identified and followed up for at least a 27-month period. Proportions and relative odds were determined for women entering and completing the ToC management pathway within recommended time frames. Results - There were 5,194 women identified as ‘eligible’ to enter the ToC management pathway. Of these, 1,916 (37%) were managed with annual Pap smears and never had a HR HPV test performed. There were 1,296 (25%) women who entered the ToC management pathway within recommended time frames, and a further 1,978 (38%) women entered outside of the recommended time frames. Overall, 961 women completed the ToC and were classified as ‘cured’ and were eligible to return to two-yearly Pap smears. Women's demographic information was significantly associated with ToC commencement, specifically, age and year of treatment, and Index of Relative Socioeconomic Disadvantage. Conclusion - Overall, a significant number of Australian women did not enter (~37%) and complete (~50%) the ToC management pathway. The challenge remains to advocate its use to practitioners to ensure women are returned to the population screening interval in a timely manner.